Studi Pengaruh Konsentrasi Co pada Struktur Kristal dan Respon Photoluminescence Film Tipis Ti1-xCoxO2 yang Ditumbuhkan dengan Teknik MOCVD - Horasdia Saragih; Pepen Arifin; Mohamad Barmawi (Institute for Research and Community Services (LPPM) ITB, 2005)
Ti1-xCoxO2 thin films have been deposited on Si substrate by MOCVD technique. Thin films were synthesized by a single plane orientation structure of anatase-213 at various to Co concentartions up to 5,77%. Photoluminescence emission spectra of thin films showed a maximum peak at the energy of 2.8 eV. These energies did not change when increasing Co concentration in the Ti1-xCoxO2 thin films up to 5.77%. The patterns of spectrum emission only differ on the intensity and broadness of spectra. Broading occurs towards the higher energy of 2.8 eV, while the intensities were increased with increasing of Co concentration.